The Impact of Parental Involvement on Students' Academic Performance: A Case Study of Secondary Schools in Sri Lanka - Abeywickrama, Rohan (English Department, Faculty of Humanities, Andalas University, 2025)
Parental involvement in students' studies at the secondary level is crucial for children’s academic success and future well-being. This study aims to explore how parental involvement impacts on the academic performance of their children both at home and school and investigate the relationship between parental involvement and students’ academic performance. A total of sixty-eight parents of secondary school students participated in the questionnaire survey, with data being collected using the convenient sampling method. Pearson correlation coefficients and multiple regression analyses were employed to identify the relations between variables. The findings revealed that factors of parent involvement-, involving in the child's homework, discussing parents' expectations of the child, appreciating the child’s achievements, creating a positive learning environment at home, and parent’s relationship with the class teacher and with the other parents-have a strong relationship with students’ academic performance. Conversely, findings also show that traditional forms of parental involvement, such as attending parent-teacher meetings and supporting extracurricular activities, have no significant connection with academic achievement. The study concludes that a comprehensive approach to parental involvement- including direct support, relationship-building, and community connections- collectively contributes to improved academic performance for students. These findings point to the need for a network of socially supportive parents, which could improve children's entire academic experience.